2018
DOI: 10.21037/shc.2017.10.03
|View full text |Cite|
|
Sign up to set email alerts
|

Annual report of Department of Thoracic Surgery at Shanghai Chest Hospital

Abstract: Alkaloids U 0600Biomimetic Total Syntheses of Cassiarins A (Ia) and B (II). -Due to the high antiplasmodial effects of the title compounds, analogues (Ib)-(Id) are prepared for structure-activity studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…20 In ultra-high volume centres (UHVC) now emerging in China, the perioperative mortality of thoracic surgery is now less than 0.1%. 21,22 Besides safety, feasibility is also well proven with case series experience. Even in the early years of VATS, increasing complex lung cancer resections have been shown to be achievable with VATS.…”
Section: The Evolution Of Evidence For Vatsmentioning
confidence: 93%
See 1 more Smart Citation
“…20 In ultra-high volume centres (UHVC) now emerging in China, the perioperative mortality of thoracic surgery is now less than 0.1%. 21,22 Besides safety, feasibility is also well proven with case series experience. Even in the early years of VATS, increasing complex lung cancer resections have been shown to be achievable with VATS.…”
Section: The Evolution Of Evidence For Vatsmentioning
confidence: 93%
“…In Japan, the 30‐day mortality rate from major lung cancer surgery is nowadays only 0.48% 20 . In ultra‐high volume centres (UHVC) now emerging in China, the perioperative mortality of thoracic surgery is now less than 0.1% 21,22 …”
Section: The Evolution Of Evidence For Vatsmentioning
confidence: 99%
“…Median sternotomy has long been the standard approach for surgical resection of thymic malignancies. But thoracoscopic surgery is increasingly used for the treatment of earlystage thymic tumors in recent years (2,3,9,18,19). A variety of studies suggested that it is associated with comparable R0 resection rate and non-inferior survival, in addition to less post-operative complications, less blood loss, shorter length of hospital stay compared to open surgery (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…The actual 30-day mortality rate from major lung cancer surgery is now only 0.48% in Japan (51). In ultra-high-volume centers (UHVCs) now emerging in China, the peri-operative mortality of thoracic surgery is now less than 0.1% (52,53). Mortality and significant morbidity from lesser wedge resections are almost non-existent amongst normal-risk patients nowadays.…”
Section: "Why Are We Avoiding Surgery For Diagnosis?"mentioning
confidence: 99%
“…Because screening detected lung nodules and GGOs frequently all these criteria for good survival, they are ideal for sublobar resection with curative intent. Indeed, the rate of performing segmentectomy has seen a marked increase in recent years, particularly in East Asia (52,53).…”
Section: "Why Are We Giving Up On the Golden Opportunity For Surgical Treatment?"mentioning
confidence: 99%